Shape Memory Polymers in Tissue Engineering Scaffolds - Liu, Benben (Transactions on Environment, Energy and Earth Sciences, 2026)
In recent years, driven by the pursuit of minimizing surgical trauma, minimally invasive procedures and related medical techniques have advanced rapidly. Among the medical devices employed in such procedures, shape memory polymer (SMP) scaffolds have gained widespread application in tissue repair due to their shape memory effect, high biocompatibility, and degradability. This study analyzes and compares the performance and fabrication processes of different SMP scaffolds, along with the impact of functionalization modifications on degradation properties. Several typical application cases are examined. Finally, the limitations of SMP scaffolds in tissue repair and potential improvement directions are discussed. This study provides a systematic theoretical basis and technical reference for the development of a new generation of high-performance tissue engineering scaffolds. The results have important guiding value for promoting the personalized design and clinical application of minimally invasive repair materials for translation. In the future, the results can be used to break through the key technological bottlenecks in the precise control of degradation rate and optimization of biological activity.
Keywords: Shape-memory polymer (SMP); scaffold; 4D printing; tissue repair.